SARS-CoV-2 infection in children: A 24 months experience with focus on risk factors in a pediatric tertiary care hospital in Milan, Italy - Di Pietro, Giada Maria; Ronzoni, Luisa; Meschia, Lorenzo Maria; Tagliabue, Claudia; Lombardi, Angela; Pinzani, Raffaella; Bosis, Samantha; Marchisio, Paola Giovanna; Valenti, Luca (Frontiers in Pediatrics, 2023)
Background: SARS-CoV-2 infection in children is characterized by a wide variability of expression ranging from asymptomatic to rarely, critical illness. The basis of this variability are not yet fully understood. The aim of this study was to identify clinical and genetic risk factors predisposing to disease susceptibility and progression in children. Methods: We enrolled 181 consecutive children aged less than 18 years, hospitalized with or for SARS-CoV-2 infection during a period of 24 months. Demographic, clinical, laboratory and microbiological data were collected. The development of COVID-19-related complications and their specific therapies was assessed. In a subset of 79 children, a genetic analysis was carried out to evaluate the role of common COVID-19 genetic risk factors (chromosome 3 cluster; ABO blood group system; FUT2, IFNAR2, OAS1/2/3 and DPP9 loci). Results: The mean age of hospitalized children was 5.7 years, being 30.9% of them under one year of age. The majority of children (63%) were hospitalized for reasons different than COVID-19 and incidentally tested positive for SARS-CoV-2, while 37% were admitted for SARS-CoV-2 infection. Chronic underlying diseases were reported in 29.8% of children. The majority of children were asymptomatic or mild symptomatic; only 12.7% developed a moderate to critical disease. A concomitant pathogen, mainly respiratory viruses, was isolated in 53.3%. Complications were reported in 7% of children admitted for other reasons and in 28.3% of those hospitalized for COVID-19. The respiratory system was most frequently involved, and the C reactive protein was the laboratory test most related to the development of critical clinical complications. The main risk factors for complication development were prematurity (RR 3.8, 95% CI 2.4-6.1), comorbidities (RR 4.5, 95% CI 3.3-5.6) and the presence of co-infections (RR 2.5, 95% CI 1.1-5.75). The OAS1/2/3 risk variant was the main genetic risk factor for pneumonia development (OR 3.28, 95% CI 1-10.7; p value 0.049). Conclusion: Our study confirmed that COVID-19 is generally less severe in children, although complications can develop, especially in those with comorbidities (chronic diseases or prematurity) and co-infections. Variation at the OAS1/2/3 genes cluster is the main genetic risk factor predisposing to COVID-19 pneumonia in children.